Technology Entrepreneurship Project (ENT 600) : Reckitt Benckiser Group PLC. / Mohd Hariz Faiz Mohd Fazli - Mohd Fazli, Mohd Hariz Faiz (2021)
In this ENT600 case study, I was given an opportunity to conduct a study on a company in which manufactured a product related to my product of interest that I wanted to develop. In this case is Dettol which is manufactured by Reckitt Benckiser Group Plc. So, the product that I want to develop in this study is the Natural Anti-Bacterial Soap Sheet which is made from natural ingredient from plant extract that can act similarly as an antiseptic like Dettol soap. In order to develop the product, I have conducted the SWOT analysis on the company to determine their Strength, Weakness, Opportunities and Threats. Based on the SWOT analysis, I can point out the weaknesses and the disadvantages of the Dettol antibacterial soap which is consists of two major problem. The Dettol product formulation can cause burning sensation to the users skin since it contain toxic chemical called Chloroxylenol. Also, most of the Dettol product are in form of soap bar and if liquid, is stored in plastic container which is less portable. The findings give me the clear vision to came up with proper idea, in order to solve the problem. In this case, I recommend replacing the use of chloroxylenol with the natural chemical contain antiseptic property extracted from the plant. Also, the physical form of soap will be converted into paper-like substances by using water soluble paper which is eco-friendly. This improvement of the product can make the user to feel safe while using the produc